2017
DOI: 10.1152/ajpregu.00095.2017
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of angiotensin-converting enzyme inhibition versus angiotensin II receptor blockade on cardiac sympathetic activity in patients with heart failure

Abstract: The beneficial effects of angiotensin-converting enzyme (ACE) inhibitors and angiotensin II (ANG II) receptor antagonists in patients with heart failure secondary to reduced ejection fraction (HFrEF) are felt to result from prevention of the adverse effects of ANG II on systemic afterload and renal homeostasis. However, ANG II can activate the sympathetic nervous system, and part of the beneficial effects of ACE inhibitors and ANG II antagonists may result from their ability to inhibit such activation. We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…ARBs produce reflexive increases in plasma renin activity and ineffective Ang II, resulting in increased Ang-(1-7) formation. Some studies have shown neutral effects of ACE inhibitors and ARBs on measures of sympathetic tone such as plasma norepinephrine and muscle sympathetic nerve activity in clinical populations [72,73,37,[74][75][76]. The collective literature, however, suggests that the beneficial effects of these therapies on blood pressure are, at least in part, due to cardiovascular autonomic mechanisms (Table 2) [62].…”
Section: Ace Inhibitors and Angiotensin Receptor Blockersmentioning
confidence: 99%
“…ARBs produce reflexive increases in plasma renin activity and ineffective Ang II, resulting in increased Ang-(1-7) formation. Some studies have shown neutral effects of ACE inhibitors and ARBs on measures of sympathetic tone such as plasma norepinephrine and muscle sympathetic nerve activity in clinical populations [72,73,37,[74][75][76]. The collective literature, however, suggests that the beneficial effects of these therapies on blood pressure are, at least in part, due to cardiovascular autonomic mechanisms (Table 2) [62].…”
Section: Ace Inhibitors and Angiotensin Receptor Blockersmentioning
confidence: 99%
“…However, due to the complexity of the detection method, MSNA technology is not widely used in the daily clinical setting. With the development of isotope tracing technology, total body and cardiac sympathetic activities could be estimated using the norepinephrine spillover technique [11]. Tritium norepinephrine is injected from peripheral vein for 20 min to stabilize the plasma concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Tritium norepinephrine is injected from peripheral vein for 20 min to stabilize the plasma concentration. Norepinephrine clearance and spillover rates are calculated according to a formula [11]. This technique was more accurate than catecholamine alone in assessing sympathetic neurotransmitter release.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that variations in the sympathetic derive observed in cardiac failure. In these types of observation physician may sometimes prescribe Beta blocker to reduces the cardiac effects of epinephrine [19,20]. Many clinical trials are also conducted to prove the additive role of beta-blockers with ACE inhibitors [21].…”
Section: Discussionmentioning
confidence: 99%